The up‐to‐11‐year survival and success of implants and abutment teeth under solely implant‐supported and combined tooth-implant‐supported double crown‐retained removable dentures - Fobbe, Hannah; Rammelsberg, Peter; Lorenzo Bermejo, Justo; Kappel, Stefanie (Clinical oral implants research, 2019)
Objective - This retrospective analysis was designed to compare the survival and success of dental implants in solely implant‐supported, double crown‐retained removable dentures (DCRDs) and combined tooth–implant‐supported DCRDs, due to a lack of data on the latter.